RANCANG BANGUN SISTEM INFORMASI JASA SERVICE AC DI KOTA BATAM BERBASIS WEB - Pandiangan, Satria; Tukino, Tukino (Computer Science and Industrial Engineering, 2023)
The goal of creating a web-based information system about air conditioning services in Batam City is to provide air conditioning services in Batam City. Web-based information systems come in the form of images, text, graphics, and sound. That's why it makes advertising or promotion more attractive. In addition, the web-based ac service information system becomes a comprehensive information system for users or visitors that can be found anywhere. This support is inseparable from the design and technology of the research process. For other media, the success of the media is determined by the success of the well conveyed message. This study aims to design a web-based information system for air conditioning services in Batam city as a source of information to find air conditioning services with other facilities in Batam. Batam City's service system is developed using PHP programming language and data is stored in a database using HeidiSQL to optimize system and database performance. The Google Maps API is one of the features of this information system that can be used to add maps. The result of the design is in the form of a web-based information system for ac services, which is expected to be the means of service delivery and other ac service facilities in Batam city, thus , through this web design, hope that there will be a similar system to create better services. and more comprehensive than existing services. .